DETERMINAN FAKTOR PEMBELIAN MIXUE ICE CREAM & TEA - Salamah, Nunung Umi; Asteria, Beta (Unitri Press, 2023)
Purpose: The aim of this exploration is to describe the impact of price, product quality and service quality on the decision to purchase Mixue Ice Cream Tea on consumers in the city of Yogyakarta, Methods: This exploration is quantitative by distributing questionnaires. The sample was 104 respondents, Analysis data: The data analysis technique used is descriptive and multiple linear regression., Result and discussions: The results of the regression coefficient are interpreted to mean that the positive influence of the three variables shows that sales will increase by 0.054 points when the added value of the price variable increases by one point. Sales will increase by 0.379 points for each increase in product quality score. Sales increased 0.143 for every point increase in the value of the service quality variable., Conclusion: This exploration proves that product quality and service quality have a positive and significant impact on consumers' purchasing decisions for Mixue Ice Cream Tea in the city of Yogyakarta. Meanwhile, prices do not have a positive impact on Mixue Ice Cream Tea consumers in the city of Yogyakarta.,